Local communities' perceptions towards economic impacts from ecotourism development in Sungai Kampar, Gopeng, Perak - Teo, Wen Qiang (2016)
The tourism development in Sungai Kampar in Gopeng, Perak has brought changes to the local community. These changes regarded as an important benefit to them. A household survey based on sample of 132 respondents in 3 villages near with the Sungai Kampar was conducted in for 1 weeks. A descriptive analysis was carried out to identify the socio demographic of local community in Sungai Kampar, Gopeng, Perak. Besides that, a Multiple Regression analysis was carried out to identify the respondents’ perception of economic impacts from ecotourism development in Gopeng, Perak. Finding from data analysis, show that positive relationship between perceptions towards income opportunities and community facilities from ecotourism development. Based on the finding from data analysis show that ecotourism development was bring more economic benefits towards local community in term of income opportunities and community facilities. On the others hands the local authorities and government were playing important role in making the region more attractive to tourists and to maintain the increasing number of tourist that will keep coming to the destination and at the same time local community be able to get benefit from it. The development authority should carry out with a properly strategy and planning, for creating a sustainability empowerment management.